Systemic Sclerosis and Multiple Cancers of the Female Genital Tract: Prolonged Survival following Current Treatment Strategies - Georgios Androutsopoulos; Georgios Adonakis; Athanasios Tsamandas; Andreas Andonopoulos; Georgios Decavalas (Case Reports in Rheumatology)
Background. Systemic sclerosis is a rare, chronic, multisystem, and autoimmune disease. There is an overall increased risk of malignancy in patients with systemic sclerosis. However, multiple cancers of the female genital tract in patients with SSc are a very rare event. Our aim is to present a case of SSc and multiple cancers of the female genital tract, with prolonged survival following current treatment strategies. Case. The patient, a 43-year-old nulliparous premenopausal Greek woman suffering from systemic sclerosis, presented with a history of abdominal pain and abnormal uterine bleeding. She underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, total omentectomy, appendectomy, and pelvic lymph node dissection. The histopathology revealed synchronous primary cancers of the endometrium and left ovary. The final diagnosis was stage Ib endometrial cancer endometrioid type and stage IIIc ovarian cancer endometrioid type. She underwent postoperative adjuvant chemotherapy and remains well without evidence of disease 89 months after initial surgery. Conclusion. Although our patient was diagnosed at advanced stage disease, prolonged survival may be related with radical surgery and postoperative adjuvant chemotherapy according to current treatment strategies.